Rethinking good governance: holding to account India's punlic institutions - Rai, Vinod (New Delhi Rupa, 2019)
Public institutions support good governance, which, in turn, promotes sustainable economic development and, thereby nurtures the welfare of the people. The vital bond between a people and its government is that of trust, and these public institutions help maintain that trust.